THE EFFECT OF DUAL ROLE CONFLICT AND SELF EFFICACY ON THE PERFORMANCE OF FEMALE EMPLOYEES AT PT. PORT OF INDONESIA (PERSERO) REGIONAL 4 MAKASSAR - Nur Intan Vadila; Samsul Rizal; Irwan Abdullah (CV. AFDIFAL MAJU BERKAH, 2024)
The purpose of this research is a type of quantitative research with the aim of knowing the influence of dual role conflict and self efficacy on the Performance of Female Employees at PT. Indonesian Harbor (Persero) Regional 4 Makassar. This sample was taken from the PT. Indonesian Harbor (Persero) Regional 4 Makassar. The type of data used in this study is quantitative data obtained from distributed questionnaires and is related to the problem under study. Data collection was carried out by observing and distributing questionnaires. In this study, the data sources used in data collection include primary data and secondary data. The research instrument used in this study uses the Likert scale method. Based on the results of data research using statistical calculation through the Statistical Package for the Social Science (SPSS) application version 26 regading The influence of dual role conflict and self-efficacy on the performance of female employees at PT. Indonesian Harbor (Persero) Regional 4 Makassar which has been discussed in the previous chapter, the author draw an important conclusion, namely Dual roles and self-efficacy have a positive and significant effect on the performance of female employees. The work pressure given by companies to female employees needs to be given more attention, because excessive work pressure will trigger multiple role conflicts which have an impact on employee performance. Apart from that, self-efficacy needs to be increased further for each individual employee.